2012
DOI: 10.1038/bjc.2012.305
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of screen-detected and interval colorectal cancers in the Bowel Cancer Screening Programme

Abstract: Background:The NHS Bowel Cancer Screening Programme (BCSP) offers biennial faecal occult blood testing (FOBt) followed by colonoscopy after positive results. Colorectal cancers (CRCs) registered with the Northern Colorectal Cancer Audit Group database were cross-referenced with the BCSP database to analyse their screening history.Methods:The CRCs in the screening population between April 2007 and March 2010 were identified and classified into four groups: control (diagnosed before first screening invite), scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
58
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 15 publications
10
58
1
Order By: Relevance
“…A population-based study conducted in Manitoba, Canada, found no survival difference between detected and interval cancers 6. In contrast, a study of the UK National Health Service Bowel Cancer Screening Programme that compared screen-detected cancers (based on positive faecal occult blood testing) against non-screen-detected cancers including interval cancers, did find a significant survival difference between the two groups 21. Although a statistical comparison between interval cancers and screen-detected cancers is not specifically reported, the respective survival curves suggest that they may be associated with a worse survival.…”
Section: Discussionmentioning
confidence: 94%
“…A population-based study conducted in Manitoba, Canada, found no survival difference between detected and interval cancers 6. In contrast, a study of the UK National Health Service Bowel Cancer Screening Programme that compared screen-detected cancers (based on positive faecal occult blood testing) against non-screen-detected cancers including interval cancers, did find a significant survival difference between the two groups 21. Although a statistical comparison between interval cancers and screen-detected cancers is not specifically reported, the respective survival curves suggest that they may be associated with a worse survival.…”
Section: Discussionmentioning
confidence: 94%
“…UK and other studies of population-based bowel cancer screening programmes [5][6][7][8][9][15][16][17] have consistently reported that interval cancers following negative faecal occult blood screening tests (both gFOBt and faecal immunochemical tests, FIT) tend to be found more often in women, in the right (proximal) colon and rectum, and to be of higher stage than cancers detected by screening; our results for site and stage are consistent with their findings (as is the overall sensitivity of screening). Our results also suggest that cancers of rarer morphologies (mucinous, signet ring cell, neuroendocrine and squamous) are more likely to be detected as interval cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Some features of screen-detected and interval colorectal cancers have been reported from England 6,7 and from the similar screening programme in Scotland, 5,8,9 but the screening programmes collect only limited information on individual participant characteristics which may be related to cancer detection. Using data from the NHS Bowel Cancer Screening Programme with electronic linkage to an on-going large UK prospective cohort, the Million Women Study, we report here tumour characteristics, including stage, grade, location and morphology, and relationship with lifestyle and other personal factors, for colorectal cancers detected at screening and in the interval between screens among 630,000 women screened in England between 2006 and 2012.…”
Section: Introductionmentioning
confidence: 99%
“…In assessing the efficacy of colorectal cancer screening, previous work has examined differences between screen-detected and nonscreen-detected disease and has shown improved survival in patients with screendetected disease [21][22][23][24][25][26][27]. Such analysis has, however, focused on the stage and site of tumours, and only one such study has included detailed analysis of adverse tumour factors beyond TNM stage that are of independent prognostic significance [21].…”
Section: Introductionmentioning
confidence: 99%